2018
DOI: 10.1039/c7nr07567g
|View full text |Cite
|
Sign up to set email alerts
|

Free chargesversusexcitons: photoluminescence investigation of InGaN/GaN multiple quantum well nanorods and their planar counterparts

Abstract: Photoexcited carriers are mainly excitons in InGaN/GaN multiple quantum well planar layers while free electron holes are greatly increased in nanorods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This means that here the carrier densities are low enough, so that exciton radiative emission rate does not grow exponentially with density, as it is usually observed in polar heterostructures. 16,17,[25][26][27][28] In conclusion, we have shown that dipolar excitons can be efficiently trapped in the plane of GaN/(AlGa)N QWs. In previous works on GaN QWs hosting dipolar excitons, the mutual repulsion of excitons led to a fast radial expansion and dilution of the exciton gas, accompanied by dramatic variation of the exciton energy and lifetime.…”
Section: (C))mentioning
confidence: 68%
See 1 more Smart Citation
“…This means that here the carrier densities are low enough, so that exciton radiative emission rate does not grow exponentially with density, as it is usually observed in polar heterostructures. 16,17,[25][26][27][28] In conclusion, we have shown that dipolar excitons can be efficiently trapped in the plane of GaN/(AlGa)N QWs. In previous works on GaN QWs hosting dipolar excitons, the mutual repulsion of excitons led to a fast radial expansion and dilution of the exciton gas, accompanied by dramatic variation of the exciton energy and lifetime.…”
Section: (C))mentioning
confidence: 68%
“…12,13 While excitons in GaN-based nanostructures have relatively high binding energies and small Bohr radii 21 (as compared to GaAs-based structures) and thus could exhibit quantum properties at higher temperatures, 22 the additional challenges that must be faced to achieve such degree of control are numerous. These may include nonradiative losses, 23 megavolt per centimeter-strong built-in electric fields, 24 an exponential dependence of the lifetime on the exciton density under high excitation conditions, [25][26][27] and the guided-and-scattered light that must be distinguished from the exciton photoluminescence (PL). 17,28 In this letter we overcome those challenges and report on the realization of ∼ 10 µm ×50 µm-size thermalized exciton fluid, trapped in the plane of a GaN/(GaAl)N quantum well grown on a free-standing GaN substrate.…”
mentioning
confidence: 99%
“…Figure a is the steady‐state PL spectra of the MAPbBr x I 3‐ x microplatelets before and after probing laser scanning (488 nm at 200 mW cm −2 ) via a confocal laser scanning microscope. The light path of the microscope is shown in Figure S1 in the Supporting Information, and other laser set‐up details are also provided in the Experimental Section in the Supporting Information. The pristine PL of microplatelets peaks at 550 nm.…”
mentioning
confidence: 99%
“…Furthermore, the special properties of nanostructures that carriers and photons are confined in the transverse directions and propagate freely in longitudinal direction [20][21] can produce special optical phenomena. In addition, some reports [22][23] on 3D PL imaging on the In 0.18 Ga 0.82 N/GaN MQW NRs are helpful for understanding the optical properties. In order to study the optical phenomena of nanorods, a confocal laser scanning microscope (CLSM) can be used to perform 3D scanning to understand the interaction between light and nanostructures.…”
Section: Introductionmentioning
confidence: 99%